Dimensional Characteristics of Figure of Pa Nangan (Mr. Hand) - Sutomo, Nur Fatimah (PT. Alahyan Publisher Sukabumi, 2023)
Wayang Sukuraga has become a symbol of art for the City of Sukabumi. The Uniqueness of Wayang Sukuraga is able to present a wayang form that is unusual from the others, presenting the wayang form from parts of the body such as hands, eyes, ears, legs, and other body parts. Wayang Sukuraga also carries messages in every character and story. One of the characters who has an important role in the Wayang Sukuraga story is Pa Nangan who represents the shape of the hand and is the object of this paper for research based on the character dimensions This study used a qualitative research method by conducting interviews with the creator of Wayang Sukuraga, Mr. Effendi. The purpose of writing this research is to see how the character of Pa Nangan is in the form of 3 Dimensional Characters, to increase knowledge in the field of wayang art and literature. The character dimension of the Pa Nangan character will include the physiological dimension relating to things attached to the form of wayang, the sociological dimension includes the social life of the Pa Nangan character, and the psychological dimension includes psychology and the message conveyed by the Pa Nangan character.